PERAN EDUKASI STUNTING TERHADAP PENGETAHUAN PADA IBU YANG MEMPUNYAI ANAK STUNTING - Fachry Rizky Maulana; Chairunnisa Melani Putria; Ilham Rizq Fauzan; Fadhillah Firdaus; Yuggo Afrianto (JPMUJ, 2024)
The cause of stunting in children is generally related to the poor nutritional status of pregnant women so the nutrition received by the fetus in the womb is insufficient. This lack of nutrition will inhibit fetal growth and can continue after birth and be the cause of stunting in children. The design of this research is a literature review. The type of data used is secondary data. The data source in this literature review research was obtained through a trusted journal search site, Google Scholar. The analytical method used is content analysis of document journals using online research journals obtained through trusted journal search sites. The incidence of stunting occurs due to several factors including unbalanced nutritional intake in children, the quality of pregnancy in mothers, and failure to care for children who are pregnant—experiencing stunting. This means that to reduce the incidence of stunting in Indonesia, there needs to be interventions that can reduce the risk of stunting in children. Based on the results of a review of several journals regarding the influence of education on the knowledge and attitudes of mothers who have stunted children, it was found that Stunting Education for mothers with stunted children Stunting can affect the quality of mothers' attitudes and behavior in caring for stunted children. This is highly recommended to increase knowledge and improve the quality of children's growth so that the incidence of stunting in Indonesia decreases significantly.